Witching days and abnormal profits in the us stock market - Guglielmo Maria Caporale; Alex Plastun (Cogent Economics & Finance, 2023)
This paper examines price effects related to witching days in the US stock market using both weekly and daily data for three major indices, namely the Dow Jones, S&P500 and Nasdaq, over the period 2000-2021. First it analyses whether or not anomalies in price behaviour arise from witching by using various parametric (Student's t-test, and ANOVA) and non-parametric (Mann-Whitney) tests as well as an event study method and regressions with dummies; then it investigates whether or not any detected anomalies give rise to profit opportunities by applying a trading simulation approach. The results suggest the presence of the anomaly in daily returns on witching days which can be exploited by means of suitably designed trading strategies to earn abnormal profits, especially in the case of the Nasdaq index. Such evidence is inconsistent with the Efficient Market Hypothesis (EMH).
Keywords: C63; G12; 330; Abnormal Returns; Anomalies; Stock Markets; Trading; Witching Days